Tales of the unexpected: Discussing improvisational learning. Issue 5 (November 2015) - Cunha, Miguel Pina e; Neves, Pedro; Clegg, Stewart R; Rego, Arménio
Improvisation has been treated largely as if it were a conceptual monolith: all improvisations are similar. We challenge this theorizing by distinguishing forms of improvisation in organizations (semi-structured, episodic, subversive, resistive) and by exploring ways in which these forms interrelate in improvisational sequences. Improvisation is not just something individuals do; it is a learned capacity that organizations can manage. We introduce the dimension of improvisational formality and informality, adding a political dimension to the study of the topic. By combining forms in process sequences, we organize the existing literature under a systematic perspective facilitating theory development via an integrative understanding of how improvisation produces learning.